1967
DOI: 10.1039/j39670000361
|View full text |Cite
|
Sign up to set email alerts
|

The garryfoline–cuauchichicine rearrangement: a study of the mechanism in the (–)-kaurenols

Abstract: The mechanism of the garryfoline-cuauchichicine rearrangement has been investigated using the epimeric (-)kaur-16-en-15-ols as models. The 15s-01 is shown to rearrange rapidly in mineral acid at room temperature to 16R-(-)-kaur-l5-one by a 15,16-hydride shift. The 16a-01, like veatchine, is stable under these conditions.The contrast in the ability of these epimeric alcohols to undergo 15,16-hydride shifts is discussed.Under the same conditions, (-)-kaur-l5-en-I 7-01 gives the allylic isomer, (-)-kaur-l6-en-I 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…Within the ferrocenyl moiety, the C--C bond lengths in the substituted cyclopentadienyl ring range from 1.403 (4) to 1.426 (3) A [mean 1.420 (3) A] while those in the unsubstituted ring lie in the range 1.384 (5) to 1.411 (6),~, [mean 1.397 (5),4,]. Such differences between the substituted and unsubstituted rings have been noted previously (Barnes, Bell, Glidewell & Howie, 1990). The other interatomic distances within the ferrocenc fragment are typical of their types.…”
Section: Commentsupporting
confidence: 65%
“…Within the ferrocenyl moiety, the C--C bond lengths in the substituted cyclopentadienyl ring range from 1.403 (4) to 1.426 (3) A [mean 1.420 (3) A] while those in the unsubstituted ring lie in the range 1.384 (5) to 1.411 (6),~, [mean 1.397 (5),4,]. Such differences between the substituted and unsubstituted rings have been noted previously (Barnes, Bell, Glidewell & Howie, 1990). The other interatomic distances within the ferrocenc fragment are typical of their types.…”
Section: Commentsupporting
confidence: 65%
“…The survey revealed that there is only one crystal structure possessing any of the investigated thioketones. In this structure (refcode: JEPVIJ [48] ), thioketone 5 acts as a ligand to Cr(CO) 4 the Fc substituent are rotated by 18.1 , which points to its in-between conformation, neither eclipsed nor staggered. The τ Ph value of 5 is very close to one of the τ Ph angles measured for the crystal structure of diphenyl thioketone (τ Ph = 317.4 and 328.1 ; refcode: THBZPS10 [49] ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the effect of oxygen in this polymerization is twofold: on the one hand, it generates peroxides (so creating the species responsible for polymerization); on the other hand it tends to inhibit the polymerization .through addition to the monomer. 5 The amount of peroxides present in the monomer also has a great influence on the intrinsic viscosities. Experiments in which H2SO4 was replaced by HC104 or HCl were negative, indicating that the mechanism of initiation involves the participation of the sulfuric moiety of the acid.…”
Section: Resultsmentioning
confidence: 99%